Description of two new species from China in a new species group of the fig wasp genus Sycophaga Westwood (Hymenoptera: Chalcidoidea: Agaonidae: Sycophaginae) - Liu, Yang; Li, Zi; Jia, Lingyi; Huang, Dawei (Zootaxa, 2016)
A new species group, the brevis-group, is established for two new species of the fig wasp genus Sycophaga Westwood (Hymenoptera: Agaonidae) reared from the monoecious fig tree Ficus orthoneura (Moraceae, Ficus, subgenus Urostigma) in China. The two new species, S. brevis n. sp. and S. diutius n. sp. are described and illustrated, supplemented by COI sequence data. In contrast with two other species groups newly recognized in Sycophaga, the explorator-group for species previously classified in Apocryptophagus Ashmead and the sycomori-group for other species previously classified in Sycophaga, the brevis-group is uniquely defined by the long pronotum of females and a Ficus host within the subgenus Urostigma.